The Effect of Sales Visits and Customer Awareness Through Relationship Marketing on Business Partners’ Intention to Collaborate with PT Pelabuhan Tanjung Priok - Ellen Rumintang; Sofwan Farisyi; Zaenal Abidin; Dian Artanti Arubusman; Lira Agusinta (Dinasti Review, 2025)
Maritime transportation plays a vital role in supporting connectivity and economic growth in Indonesia as an archipelagic nation. Ports, as the main hubs of maritime transportation, are required to provide efficient and high-quality services to maintain customer satisfaction and loyalty. PT Pelabuhan Tanjung Priok (PTP), as a provider of multipurpose terminal services, has implemented various marketing strategies, including sales visits, increasing customer awareness, and applying relationship marketing. However, the results of the 2022 customer engagement survey showed fluctuations in some branches, and cargo traffic realization only reached 79.22% of the RKAP target, indicating the need to evaluate the effectiveness of existing marketing strategies. This study aims to analyze the influence of sales visits and customer awareness through relationship marketing on business partners' interest in collaborating with PT Pelabuhan Tanjung Priok. The selection of variables is based on theoretical and empirical relevance, where sales visits are considered important in building direct interaction and trust, customer awareness influences perception and interest in using services, while relationship marketing focuses on establishing mutually beneficial long-term relationships. This study uses quantitative methods with SEM PLS analysis. The results show that relationship marketing mediates sales visits and customer awareness on the interest of business partners in collaborating with PT Pelabuhan Tanjung Priok.